(untitled) (The Agriculturists, 2018)
The present study was conducted to estimate the profitability, domestic resource cost (DRC) and comparative advantages of lentil and mustard production in Bangladesh. Primary data were used in this study, where a total of 100 randomly selected farm survey (Mustard 50 & Lentil 50) was conducted in Meherpur district using structured questionnaire. The study revealed that per hectare total cost and net profit of lentil production were about Tk. 78,442 and Tk. 86,590, respectively, whereas they were Tk. 62,527 and Tk. 38,718 for mustard production. The benefit cost ratios (BCR) of lentil and mustard production were 2.32 and 1.73, respectively, indicating that both lentil and mustard cultivation in Bangladesh are profitable. The domestic resource costs (DRC) of lentil and mustard production were 0.39 and 0.55, respectively which imply that Bangladesh has comparative advantage in producing both lentil and mustard. The Cobb-Douglas production function coefficients show that farm area, irrigation, pesticides, and chemical fertilizers (Gypsum, MP) were statistically significant factors affecting lentil production having increasing returns to scale. Farm area, irrigation and manure were statistically significant factors affecting mustard production with constant return to scale. In this study, production, technology and marketing problems have been listed down which will help the policy makers and the researchers to undertake proper steps for further improvement of lentil and mustard production in Bangladesh. The Agriculturists 2018; 16(1) 21-33